The arachidonate 5-lipoxygenase activating protein gene polymorphism is associated with the risk of scleroderma-related interstitial lung disease: a multicentre European Scleroderma Trials and Research group (EUSTAR) study. (4th February 2017) - Kowal-Bielecka, Otylia; Chwiesko-Minarowska, Sylwia; Bernatowicz, Pawel L.; Allanore, Yannick; Radstake, Timothy; Matucci-Cerinic, Marco; Broen, Jasper; Hesselstrand, Roger; Krasowska, Dorota; Riemekasten, Gabriella; Vonk, Madelon; Kowalczuk, Oksana; et al.
Abstract: Objectives. The arachidonate 5-lipoxygenase activating protein (ALOX5AP) regulates synthesis of leukotrienes (LTs), which are important mediators of inflammation and connective tissue remodelling. The aim of this study was to evaluate if single nucleotide polymorphisms (SNPs) of ALOX5AP confer risk of SSc and/or SSc-related organ involvement. Methods. Seven SNPs of ALOX5AP (rs17222814, rs17216473, rs10507391, rs4769874, rs9551963, rs9315050 and rs7222842) were genotyped in a cohort of 977 patients with SSc and 558 healthy controls from centres collaborating within the European Scleroderma Trials and Research group. In 22 SSc patients, concentrations of cysteinyl LTs and LT B4 (LTB4) were measured in the supernatants of ionophore-stimulated peripheral blood mononuclear cells (PBMCs) by means of commercially available enzyme immunoassay kits. Results. Significant association was found between rs10507391 polymorphism (T/A) of ALOX5AP and the risk of SSc [odds ratio (OR) 1.27 (95% CI 1.07, 1.50), P < 0.05 vs controls], the presence of SSc-related interstitial lung disease on high-resolution CT of the lungs [OR 1.45 (95% CI 1.17, 1.79), P < 0.05 vs patients without SSc-related interstitial lung disease] as well as with restrictive ventilatory defect [forced vital capacity <70% of predicted; OR 1.51 (95% CI 1.16, 1.97), P < 0.05 vs SSc patients without pulmonary restriction]. PBMCs from SSc carriers of rs10507391 allele A synthesized greater amounts of cysteinyl LTs as compared with SSc patients with rs10507391 TT genotype ( P < 0.05). Synthesis of LTB4 did not differ significantly between the two groups. Conclusion. The results of our study indicate that the genetic variants of ALOX5AP might play a role in the development of SSc-related pulmonary fibrosis.